Pragmatic functions of evidentiality in diplomatic discourse: Toward a new analytical framework - Xu, Zhongyi (Frontiers in Psychology, 2022)
This paper examines the pragmatic functions of evidentiality categories in diplomatic discourse by illustrating a new classification of English evidentiality. It adopts a data-based approach by analyzing a corpus of thirty English political speeches from three US presidents (including Bush, Obama, and Trump). The results show that: (i) Evidentiality can be classified into three categories: personal sources; shared sources and other sources. (ii) Besides the function of (de)legitimation, evidentiality can also be used to normalize the speaker’s ideology. (iii) Shared sources of evidentials reflect the speaker’s ideological bias, because they encode the speaker’s presupposition of authority, facts, or shared knowledge. (iv) Personal sources of evidentials mean that the speaker is more willing to take verbal responsibility. (v) Other sources of evidentials reflect the speaker’s lower responsibility for the information he/she offered. (vi) The use of the three evidential sources reflects the speakers’ different responsibilities for their propositions and reveals their subjective or intersubjective stance.